Updated checklist of mayflies from northeastern Algeria with biogeographical and ecological insights (Insecta, Ephemeroptera) - Wissem Hezil; Farrah Samraoui; Abdellatif Satour; Meriem Taferghoust; Hayat Boucenna; Laurent Vuataz; Jean-Luc Gattolliat; Michel Sartori; Boudjéma Samraoui (Alpine Entomology, 2025)
Mayflies (Ephemeroptera) play a crucial role in nutrient cycling and energy transfer between ecotones, making them key indicators of freshwater ecosystem health. As part of a broader study conducted between 2018 and 2022, a survey of rivers and streams across four regions in northeastern Algeria recorded 15 mayfly species, contributing to an updated regional checklist and mapping the distribution of 36 species. Notably, ten species were putatively new to science, with nine awaiting formal description. The survey also documented two rarely recorded burrowing mayfly species and one interstitial species in North Africa, whose mass emergences serve as valuable bioindicators of riverine ecological integrity. Their close association with sediment or hyporheic zones, combined with a high sensitivity to environmental stressors, makes them effective for cost-efficient, rapid assessments of contaminants in fluvial systems. This study advances knowledge of mayfly taxonomy, biogeography, and ecology in the region while providing essential data for freshwater conservation efforts.